URGENSI PEMISAHAN KEUANGAN PRIBADI DAN USAHA DALAM PENERAPAN AKUNTANSI SYARIAH PADA UMKM DI BATAM - Widya Ayu Kusumawati; Junia Athira Putri; Fathiyah Fajri Ramadhani Siregar (Jurnal Liga Ilmu Serantau, 2026)
Micro, Small, and Medium Enterprises (MSMEs) contribute significantly to the national economy, including in Batam City. Despite their importance, many MSME actors experience difficulties in distinguishing personal finances from business finances, which negatively affects the reliability of financial statements and increases the risk of non-compliance with Sharia accounting principles. This study employs a descriptive qualitative approach using interviews, observations, and questionnaires involving MSMEs in the food and service sectors. The findings indicate that the mixing of funds is primarily driven by low financial literacy and the absence of practical and simple financial recording guidelines. As a result, financial reports tend to be inaccurate and Sharia compliance remains low. The study concludes that separating personal and business finances is a fundamental requirement for the proper implementation of Sharia accounting. Therefore, it recommends enhancing financial literacy, providing continuous assistance, and adopting appropriate bookkeeping models to support better financial management and governance.